The vicious circle mechanism in atopic dermatitis: psychological distress as cause and effect of atopic dermatitis - Nowak, Karolina; Olejarz, Zuzanna; Drygała, Zuzanna; Wyrwał, Julia; Zielińska, Zuzanna; Słowik, Magdalena; Nowak, Karolina; Nieć, Maria; Gierlach, Katarzyna; Krasuska, Martyna (Journal of Education, Health and Sport, 2024)
Introduction and purpose: Atopic dermatitis (AD) is chronic inflammatory skin disorder. It typically begins in infancy or childhood and might persist into adulthood. AD is characterized by dry, itchy, eczematous skin. The lesions can vary in intensification from mild to severe according to patient age or body region. AD requires ongoing management to control the symptoms. Skin manifestations along with the demand of treatment and care regimens significantly impact quality of life (QOL) in patients with AD. Individuals suffering from this condition are more prone to developing mental health disorders, which are often linked to emotional stress they experience. Exposure to stress exacerbates AD and stimulates skin changes, which in turn leads to intensification of treatment regimens. This cause-and-effect chain can be considered as a vicious circle mechanism. The aim of the review is to highlight the phenomenon by examining current literature on this topic in order to raise the awareness of healthcare professionals regarding this subject as well as implement appropriate and complete support for patients struggling with AD. A brief description of the state of knowledge: The pathophysiology of AD is multifactorial. Numerous studies explore the impact of stress on the deterioration of AD symptoms and delve into its pathogenic concepts. Simultaneously, researchers highlight increased psychological distress in AD patients, which surpass that observed in many other chronic conditions. Summary: Psychological factors play a significant role in AD. It demands considering mental health screening and support as a part of clinical practice, treating AD patients. Further research is necessary to provide efficient and comprehensive interventions.